Factors that Influence Intent to Share Genetic Information Related to Cancer Risk with Family Members. Issue 8 (3rd August 2021) - Stuttgen Finn, Kelsey; Pacyna, Joel E.; Tsou, Cindy; Samadder, Niloy J.; Sharp, Richard R.
Abstract: We describe factors influencing patient decisions to share positive cancer genetic test results with family members. We focused on patients who were diagnosed with several different cancer types but did not have a family history that was suggestive of an inherited risk. Participants were recruited from Mayo Clinic and had been recently diagnosed with cancer. An 80+ gene panel was performed. Before receiving genetic test results, patients completed a 49-item survey on their intent to share their results with relatives. 1, 721 (57.7%) of 2, 984 individuals who elected to pursue genetic testing completed the survey. Most patients planned to share cancer-related genetic results with a spouse or partner (97.0%), at least one adult child (92.2%), at least one sibling (86.2%), and with at least one parent (70.3%). Familial support scores and familial communication scores were predictive of intent to share cancer-related genetic test results. Our data highlight differences in family communication capacity and support that are important for clinicians to consider when supporting patients who wish to share cancer-related genetic test results with family members. Our data point to several potential interventional strategies that might increase the likelihood of cancer-related genetic test results being shared with family members at risk.